Dialog Pemikiran Islam dan Filsafat Barat: Studi atas Pemikiran Martin Heidegger - Nahdly, M. As’ad; Fahman, Ahmad Amiq (Al-Faruq: Jurnal Hukum Ekonomi Syariah dan Hukum Islam, 2024)
This study discusses the comparison between Martin Heidegger's existential thinking in Western philosophy with the Islamic view of human existence and the purpose of life. Heidegger, through the concept of Dasein, emphasizes the importance of awareness of death and time as the basis of authentic life. Meanwhile, in Islam, humans are seen as creatures created to serve God, with a life orientation centered on the afterlife. This study uses a qualitative approach and comparative analysis method to the works of Heidegger, classical Muslim philosophers, and the texts of the Qur'an and Hadith. The results of the study show that although they come from different metaphysical backgrounds, there is an important meeting point between the two views, especially in terms of awareness of the limitations of life and moral responsibility. Heidegger's thinking contributes to broadening the perspective on human authenticity, which in Islam is transformed into a life that is subject to the will of God. This study also underlines the relevance of Heidegger's existential concept in contemporary Islamic education as a reflective approach to forming self-awareness, responsibility, and a transcendental life orientation.